Sensitivity to streptomycin in varieties of barley (Hordeum vulgare) - BANSAL, SURABHI; CHAUHAN, S V S (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1992 to study the sensitivity of 7 varieties (’IC 79574’,’IC 79596’, ’Ic 82560’,’IC 82637’.’DL 3’, ’DL 100’ and ’Ratna’) of barley (Hordeum vulgare 1. sensu lato) to streptomycin, There was a marked reduction in seed germination in different varieties treated with various concentrations of streptomycin. Streptomycin @ 2 500 ppm caused the maximum reduction in seed germination (61.9%) in ’Ratna’, whereas @ 3 000 ppm showed the minimum reduction (25.1%) in ’DL 100’. Similarly, aÂ significant reduction in the growth of the seedlings (length of root and shoot) was observed, which was directly proportional to the increase in the concentration of streplomycin. ’DL 3’ showed the maximum reduction, whereas ’IC 79574’ the minimum. Based on the number of chlorophyll mutations (albinos, stripe I and stripe II) in the treated populations, ’DL 100’ and ’Ratna’ showed maximum resistance, indicating their usefulness as stress-tolerant phenotypes, which may be useful in somatic hybridization for somaclonal selection.